PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. MELIO INDOTAMA SEJAHTERA SITUBONDO - Bari, Muhammad Misbahul; Kusnadi, Edy; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The research objective is to determine the effect of work stress and work environment on employee performance with job satisfaction as an Intervening Variable at PT. Melio Indotama Sejahtera Situbondo. The sampling technique used in this study is a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that work stress has a positive and significant effect on job satisfaction, work environment has a positive and significant effect on job satisfaction, job stress has a positive and significant effect on employee performance, work environment has a negative and insignificant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, job stress has a positive but not significant effect on employee performance through job satisfaction, work environment has a positive and significant effect on employee performance through job satisfaction